BALE, AWIQ-AWIQ, AND BESIRU: An Ethnography of Sasak Local Wisdom in Sustainable Development Goals Accountability among Housing Developers on Lombok Island - Yusli Mariadi; Nungki Kartikasari (Journal of Finance, Economics and Business, 2026)
Technically and normatively oriented models of accounting integration based on the Sustainable Development Goals (SDGs) risk reducing the financial accountability of housing developers to a mere recording mechanism, failing to capture the local meanings and practical rationalities that sustain such practices in everyday life. This article employs a qualitative ethnographic approach, combined with ethnomethodology as an analytical technique, to understand how the local wisdom of the Sasak community on Lombok Island can be read as an interpretive lens on SDG-related financial accountability among housing developers, taking two developers in West Lombok Regency, PT Nata Alam Raya and PT Meka Asia Properti, as illustrative loci. The primary data for this study derive from an in-depth reading of three academic sources on Sasak traditional architecture and settlement Pawitro (2011), Sukawi and Zulfikri (2010), and Sahira et al. (2023) analyzed thematically to trace the meaning of accountability and its links to SDG targets. The findings show that the institutions of awiq-awiq, kemalik, and besiru, the principles of dwelling self-reliance (kemandirian berhuni), and material practices such as belulut have functional counterparts in modern housing-development activities ranging from site feasibility assessment and open-space management to local labor absorption and sustainable material selection that can be explicitly linked to SDG Goals 6, 8, 11, 12, and 15, as well as to specific line items in the Statement of Financial Position, the Income Statement, and the Notes to the Financial Statements of developers. This article contributes an interpretive framework that links local-wisdom-based accountability with formal accounting structures, complementing the regulation-based conceptual model developed at the earlier stage of this research.